Literature Review: Efektivitas Program K3 Dalam Meningkatkan Patient Safety Di Rumah Sakit - Fithri Handayani Lubis (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
This study aims to systematically review the effectiveness of occupational health and safety (OHS) programs in improving patient safety in hospitals. The background of this study highlights the importance of occupational safety as an integral part of healthcare quality, where failures in OHS management may not only affect healthcare workers but also directly impact patient outcomes. The method used was a systematic literature review guided by the PRISMA approach, covering articles published between 2020 and 2025. A total of 28 articles were analyzed after a rigorous screening process from 412 initial records across multiple databases. The findings reveal that OHS programs contribute to patient safety through structured training and education, transparent risk management and incident reporting systems, and the establishment of a strong safety culture. These efforts have been shown to reduce adverse events, hospital-acquired infections, and medical errors. The implications of this review highlight that strengthening OHS programs should be considered a strategic component in hospital management to achieve sustainable improvements in patient safety and quality of care.